The moderating effects of parental psychological control on the relationship between unsociability and socio-emotional functioning among Chinese children - Zheng, Hong; Hu, Yihao; Cao, Yuchen; Li, Ran; Wang, Nan; Chen, Xi; Chen, Ting; Liu, Junsheng (Frontiers in Psychology, 2024)
This study aimed to investigate the moderating effect of parental psychological control on the relationship between unsociability and socio-emotional functioning in Chinese children. A total of 1,275 students from Grades 3 to 7 (637 boys, M age = 10.78 years, SD = 1.55 years) were selected from 4 public schools in Shanghai to participate in this study. Data on unsociability, parental psychological control and socio-emotional functioning were collected from multiple sources, including selfreports and peer-evaluations. Results indicated positive associations between unsociability and peer victimization, depressive symptoms, and social anxiety, as well as a negative association between unsociability and social preference, and parental psychological control moderated these associations. Specifically, the associations between unsociability and peer victimization, social preference, and depressive symptoms were stronger, and the association between unsociability and social anxiety was only significant among children with higher level of parental psychological control. The results highlight the importance of parental psychological control in the socio-emotional functioning of unsociable children in the Chinese context, enlightening educators that improving parenting behavior is essential for children's development.